A new glanapterygine catfish of the genus Listrura (Siluriformes: Trichomycteridae) from the southeastern Brazilian coastal plains - Villa-Verde, Leandro; Costa, Wilson J.e.m. (Zootaxa, 2006)
Listrura picinguabae, new species, is described from small tributary streams of rio da Fazenda, an isolated coastal river in Picinguaba, São Paulo State, southeastern Brazil. It is distinguished from all other trichomycterids, except L. nematopteryx, in possessing a single long pectoral-fin ray. It differs from L. nematopteryx by a combination of features including relative position of anal and dorsal-fin origins, higher number of anal-fin rays and opercular and interopercular odontodes, and morphology of the urohyal.